2020
DOI: 10.21203/rs.3.rs-96205/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Surface Modification on Cellular Uptake and Cytotoxicity of Silica Nanoparticles

Abstract: Background: Silica nanoparticles (SiO2 NPs) are widely used in industrial products as additives for rubber and plastics or as filler strengthening concrete, as well as being used in the biomedical field for drug delivery and theranostic purposes. The present study investigated the effects of amino or carboxyl functionalization of rhodamine-labeled SiO2 NPs on cellular uptake and cytotoxicity. Methods: Male mice were randomly divided into seven groups (n=6, each) and exposed to non-functionalized (plain), carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Further, in the absence of FBS, like in this study, CPS20 particles, followed by CPS200, PPS20 and AMI200 particles, showed the highest rate of macrophage uptake. The preference of carboxyl-functionalized over amino-functionalized particles by macrophages appears to be independent of the particle material because it was reported for 100 nm polystyrene particles and for 25 nm silica particles [29][30][31].…”
Section: Discussionmentioning
confidence: 90%
“…Further, in the absence of FBS, like in this study, CPS20 particles, followed by CPS200, PPS20 and AMI200 particles, showed the highest rate of macrophage uptake. The preference of carboxyl-functionalized over amino-functionalized particles by macrophages appears to be independent of the particle material because it was reported for 100 nm polystyrene particles and for 25 nm silica particles [29][30][31].…”
Section: Discussionmentioning
confidence: 90%